Det kgl. Landhusholdningsselskabs Generalforsamling. Den 15de December 1893. - la Cour, J. C. (Tidsskrift for Landøkonomi, 2018)
Det kgl. Landhusholdningsselskabs Generalforsamling. Den 15de December 1893.